2018
DOI: 10.1182/blood-2018-99-111244
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results from a Phase I Study of Isatuximab (ISA) in Combination with Bortezomib, Lenalidomide, Dexamethasone (VRd), and in Patients with Newly Diagnosed Multiple Myeloma (NDMM) Non-Eligible for Transplant

Abstract: Background: Isatuximab (ISA) is an anti-CD38 monoclonal antibody with multiple modes of action for killing tumor cells via direct tumor targeting and immune cell engagement. ISA, combined with bortezomib, has demonstrated strong potentiation in a multiple myeloma (MM) xenograft model (Clin Cancer Res 2014:20:4754). This supported evaluation of ISA with bortezomib combinations in pts with newly diagnosed multiple myeloma (NDMM) ineligible for transplant. In the initial cohort, ISA combined with bortezomib, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Lastly, isatuximab is being assessed in combination with either bortezomib, cyclophosphamide, and dexamethasone or bortezomib, lenalidomide, and dexamethasone in patients with NDMM who are not eligible for, or elect not to receive transplantation (ClinicalTrials.gov, NCT02513186). Interim analysis from both arms of this trial have been reported [48,49].…”
Section: Isatuximab In Patients With Newly Diagnosed MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, isatuximab is being assessed in combination with either bortezomib, cyclophosphamide, and dexamethasone or bortezomib, lenalidomide, and dexamethasone in patients with NDMM who are not eligible for, or elect not to receive transplantation (ClinicalTrials.gov, NCT02513186). Interim analysis from both arms of this trial have been reported [48,49].…”
Section: Isatuximab In Patients With Newly Diagnosed MMmentioning
confidence: 99%
“…Patients with NDMM ineligible for transplantation were treated in an induction phase with either isatuximab 10 mg/kg or 20 mg/kg weekly (cycle 1), followed by every 2 weeks (cycles 2-12); bortezomib (1.3 mg/m 2 ) for cycles 1-12; cyclophosphamide (300 mg/m 2 ) for cycles 1-12; and dexamethasone (20 mg/day) for cycles 1-12, followed by a maintenance phase of 4-week cycles that included isatuximab at the assigned dose and dexamethasone (20 mg) on day 1 for all cycles [48]. The maintenance phase was followed by an isatuximab 10 mg/kg dose expansion phase.…”
Section: Isatuximab In Patients With Newly Diagnosed MMmentioning
confidence: 99%
“…Another phase Ib trial is evaluating induction with 12 cycles of isatuximab (10/20 mg/kg) plus bortezomib-cyclophosphamide-dexamethasone (VCd), followed by maintenance with single-agent isatuximab in a similar patient population. The ORR was 87%, whereas data on MRD status and PFS are not yet available [48].…”
Section: Isatuximabmentioning
confidence: 97%
“…In transplant-ineligible NDMM patients, isatuximab (10 mg/kg) is being evaluated in a phase Ib trial in combination with VRd as induction (4 cycles) followed by maintenance with Isa-Rd. Preliminary results showed an ORR of 93%, with 38.5% of patients achieving MRD negativity [47]. Another phase Ib trial is evaluating induction with 12 cycles of isatuximab (10/20 mg/kg) plus bortezomib-cyclophosphamide-dexamethasone (VCd), followed by maintenance with single-agent isatuximab in a similar patient population.…”
Section: Isatuximabmentioning
confidence: 99%
“…An ongoing phase I study is investigating isatuximab, in combination with VRd (Isa-VRd): the first report on 22 patients showed good tolerability, with 46% of grade ≥3 AEs, mostly hematologic. Besides, response rates are promising, with MRD negativity rates (10 −6 ) by NGS of 33% and by NGF 18% [111].…”
Section: Asct-ineligible Patientsmentioning
confidence: 98%